The Community Perceptions of Street Hawkers in Malaysia - Azis, Affauzini; Tek, Lew Xiou (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research was aimed to analyze the characteristics and community perceptions of street hawkers in Malaysia and their impact on environment. To collect the data, this descriptive qualitative research used instruments such as observation, interview and documentation. The data collected were primary and secondary data. The findings revealed street hawker characteristics and community perceptions of their existence in Malaysia.